Membentuk Jiwa Seni Siswa SD Melalui Pembelajaran Contextual Teaching and Learning - Atiyyah Maulaya; Desryan Awalia Putri; Qoriatul Hikmah; Muhammad Nofan Zulfahmi (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Fine arts learning in elementary schools has an important role in developing students' creativity and artistic spirit. This research aims to analyze the effectiveness of Contextual Teaching and Learning (CTL) in shaping the artistic spirit of elementary school students. This research uses a quasi-experimental design with an experimental group that applies CTL learning and a control group that uses conventional learning methods. The research subjects were students, and the data collection instruments included a drawing test, observation, and questionnaire. To compare the learning outcomes of both groups, the data were analyzed using t-test. The results showed significant differences between the experimental and control groups. Students who followed CTL learning showed improvement in creativity, self-expression, and understanding of fine art concepts compared to the control group. The findings indicate that CTL learning is effective in shaping students' artistic spirit, giving them the opportunity to connect learning materials with daily life through various interesting and challenging activities, which encourage them to think critically, creatively, and collaboratively. In addition, since CTL learning makes students feel more involved and active in the learning process, it can increase their motivation to learn.